2020
DOI: 10.1155/2020/7469584
|View full text |Cite
|
Sign up to set email alerts
|

A New Method for Artificial Core Reconstruction of a Fracture‐Control Matrix Unit

Abstract: The fracture-control matrix unit (F-CMU) is a special body present in low-permeability fractured reservoirs that can be distinguished by a fracture system and a matrix system. The imbibition phenomenon of the F-CMU provides the possibility for secondary development of low-permeability fractured reservoirs because of the driving force including capillary force and gravity. However, the F-CMU is difficult to obtain during the field core drilling, which has limited the development for laboratory dynamic imbibitio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Near-wellbore measurement methods often use radiotracers to monitor wellbore data (Guo et al, 2019;Liu et al, 2018;Jin et al, 2021;Liu et al, 2020a). Different radioactive materials were put into the fracturing fluids, gamma spectrum was measured by using a logging instrument, the distribution of the proppant was obtained, and then the fracture height and width were calculated (Gulrajani and Romero, 1996;Shi et al, 2017;Liu et al, 2020b), as shown in Figure 1C.…”
Section: Near-wellbore Measurement Methodsmentioning
confidence: 99%
“…Near-wellbore measurement methods often use radiotracers to monitor wellbore data (Guo et al, 2019;Liu et al, 2018;Jin et al, 2021;Liu et al, 2020a). Different radioactive materials were put into the fracturing fluids, gamma spectrum was measured by using a logging instrument, the distribution of the proppant was obtained, and then the fracture height and width were calculated (Gulrajani and Romero, 1996;Shi et al, 2017;Liu et al, 2020b), as shown in Figure 1C.…”
Section: Near-wellbore Measurement Methodsmentioning
confidence: 99%
“…The in situ visualization of instant transport phenomena becomes impossible due to the opacity of the core. Additionally, core experiments are often associated with lengthy experimental periods, cumbersome operations, and limitations in representing the multiscale matrix–fracture structure …”
Section: Introductionmentioning
confidence: 99%
“…Additionally, core experiments are often associated with lengthy experimental periods, cumbersome operations, and limitations in representing the multiscale matrix−fracture structure. 32 Microfluidic technology, with its unique advantages of customizability, real-time in situ visualization, and economic efficiency, has emerged as a potent tool for researching flow in porous media. 33,34 Microfluidic chips can serve as a dynamic complement to "petrological sheets" by simplifying the pore/ throat structure while preserving the essential characteristics of natural tight formations.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The one-dimensional core was fractured using advanced techniques such as radial extrusion and laser engraving. 19,20 Additionally, low-field nuclear magnetic resonance technology was employed to dynamically monitor the fluid saturation changes during the displacement process in FMDS. 21 While one-dimensional natural cores and cylindrical artificial cores offer improved simulation of formation heterogeneity conditions, their limited size prevents accurate and effective representation of fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…At present, physical models employed for simulating displacement processes, prognosticating productivity, and assessing the efficacy of operational measures in oil and gas field development predominantly encompass the one-dimensional sand-filled pipe/core model, 2D flat plate model, and 3D model. The one-dimensional core was fractured using advanced techniques such as radial extrusion and laser engraving. , Additionally, low-field nuclear magnetic resonance technology was employed to dynamically monitor the fluid saturation changes during the displacement process in FMDS . While one-dimensional natural cores and cylindrical artificial cores offer improved simulation of formation heterogeneity conditions, their limited size prevents accurate and effective representation of fractured reservoirs.…”
Section: Introductionmentioning
confidence: 99%